ROMANIAN AND NAVOI: TRADITION AND HERITAGE (Archive of Conferences, 2021)
This article discusses and discusses the interconnectedness and similar universal ideas in the most productive and main themes of the works of the great thinkers of the East, Mawlana Jalaliddin Rumi and Hazrat Alisher Navoi.